A New Type of Hydro-mechanical Transmission System and Experimental Analysis - Wu Songjun; Li Hua; Yao Jin (Jixie chuandong)
A new type of hydro-mechanical transmission system is designed aiming at promoting the efficiency of traditional torque converter. The traditional torque converter lacks of transmission efficiency,which is pointed out by simply introducing basic structure and theory. To solve this problem,a new kind of compound transmission system is proposed. A mechanical device is added to the traditional one,which can make torque converter always work at high efficiency condition,and hydraulic machine transfer power while the whole system is on the condition of power dividing. Finally,the efficiency variances between prototype experiment and traditional device shows this transmission system is able to promote efficiency,which provides the basis of putting this device into production.